A EXPANSÃO DA SOJA NUMA ECONOMIA DE ENCLAVE: o caso da Região Sul do Maranhão 1996-2010 - BEZERRA, Júlio César Barbosa (2014)
This research aims to demonstrate that the southern region of the state of Maranhão has all the characteristics of an enclave economy, as it is based on primary commodity exports, especially soybeans, whose production activity contributes little to the development of the economy which it belongs. The agricultural model adopted , based on the large property, led by large companies, mostly foreign capital, income concentration and focused almost exclusively for export, includes a political and economic strategy to generate foreign exchange through surpluses Brazilian trade balance in prioritizing the traditional sectors of higher productivity, particularly commodities , contributing to reprimarization exports. To understand the phenomenon, this paper makes use of classical references on the subject; studies the major transformations of the Brazilian economy from the 1930s and the economy title from the 1970s, analyzes the major agricultural soybean expansion in the country and in the southern region of Maranhão, from the large economic and political upheavals that began in the late 1980s, is used for field research that prove the few benefits provided by the soybean economy for the people of wrapped and proves the discount chain effects, are downstream or upstream of primary commodity exports in the region.